2006
DOI: 10.1507/endocrj.k05-181
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Levothyroxine on Total Lipid Profiles as Assessed by Analytical Capillary Isotachophoresis in a Patient with Hypothyroidism

Abstract: Abstract. The patient was a 51-year-old Japanese female who had been diagnosed with hyperlipidemia. At the first medical examination, her serum levels of total cholesterol (TC) and triglyceride (TG) were 482 and 205 mg/dl, respectively. Since hyperlipidemia was not improved by pravastatin, atorvastatin or niceritrol, and since the levels of thyroid-stimulating hormone (TSH) and free T4 were 730 IU/ml and 0.3 ng/dl, respectively, the patient was diagnosed as secondary hyperlipidemia with hypothyroidism. A metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Various reports suggest that administration of T 3 or T 4 (levothyroxine) to hypothyroid rats restores the change in lipid profile (Ruggiero et al, 1987;Kiya et al, 2006). However, Mogulkoc et al (2005a,b) reported that thyroxine administration to hypothyroid rats resulted in oxidative stress in several tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Various reports suggest that administration of T 3 or T 4 (levothyroxine) to hypothyroid rats restores the change in lipid profile (Ruggiero et al, 1987;Kiya et al, 2006). However, Mogulkoc et al (2005a,b) reported that thyroxine administration to hypothyroid rats resulted in oxidative stress in several tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Because the screening test is simple, the disease can be detected in its early stage with dyslipidemia [1]. Canaris et al showed that only 50% of newly diagnosed hypothyroid patients had symptoms [2].…”
mentioning
confidence: 99%
“…A study of the effects of atorvastatin and apoA‐I/phosphatidylcholine discs has shown a decrease in triglyceride‐rich lipoprotein subfractions, suggesting that their combination could be a promising therapeutic approach for hypertriglyceridemia 39. Other works examined the effects of apolipoprotein A‐I/phosphatidylcholine discs on charge‐based low‐density lipoprotein (LDL) subfractions 40, the relation between the remnant‐like particles‐cholesterol level and charge‐based apolipoprotein B‐containing lipoprotein subfractions in patients with hypercholesterolemia 41, extracellular‐signal‐regulated kinase 1/2 activity using LDL with various degrees of oxidation 42, the mechanism by which apolipoprotein A‐I/phosphatidylcholine discs increase pre‐β high‐density lipoproteins 43, the association between the level of fast‐migrating LDL subfraction and carotid‐artery intima‐media thickness 44, the effects of cholesterol feeding and simvastatin treatment on plasma platelet‐activating factor acetylhydrolyse activity 45, the association between atrial fibrillation and platelet‐activating factor acetylhydrolase 46 and the effect of levothyroxine on total lipid profiles in a patient with hypothyroidism 47. ITP was used for the determination of acetic acid (HAc) in the intestinal contents from jejunum, ileum and colon (LE: 10 mM HCl, 22 mM 6‐amino‐ n ‐hexanoic acid (EACA), 0.1% methylhydroxyethylcellulose (MHEC); TE: 5 mM caproic acid) 48.…”
Section: Analytical Applicationsmentioning
confidence: 99%